2019
DOI: 10.1017/s0956618x19000048
|View full text |Cite
|
Sign up to set email alerts
|

The Church of England and Same-Sex Marriage: Beyond a Rights-Based Analysis

Abstract: Some scholars, faced with the apparent conflict between the Church of England's teaching on marriage and the idea of equal marriage embraced by the Marriage (Same Sex Couples) Act 2013, have focused on the implications of that Act for the constitutional relationship between Church, State and nation. More frequently, noting the position of the Church of England under that Act, academics have critiqued the legislation as an exercise in balancing competing human rights. This article by contrast, leaving behind a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(2 reference statements)
0
4
0
1
Order By: Relevance
“…The study's results suggest several implications for how the Church can help support its gay employees. This research demonstrates the strength of feeling held by gay clergy with regard to the current policies which deny gay clergy the right to marry or conduct a sexual relationship (Clucas 2012;Smith 2019). Most participants displayed a level of anger and frustration with the Church and its leaders yet were resigned to the belief that the status quo will be maintained for the foreseeable future.…”
Section: Implications For Practicementioning
confidence: 82%
See 2 more Smart Citations
“…The study's results suggest several implications for how the Church can help support its gay employees. This research demonstrates the strength of feeling held by gay clergy with regard to the current policies which deny gay clergy the right to marry or conduct a sexual relationship (Clucas 2012;Smith 2019). Most participants displayed a level of anger and frustration with the Church and its leaders yet were resigned to the belief that the status quo will be maintained for the foreseeable future.…”
Section: Implications For Practicementioning
confidence: 82%
“…However, within the context of faith leadership, the psychological contract between the employee and the organisation, is perhaps a secondary consideration to what could be considered to be a 'spiritual contract', between the employee and God. It could therefore be suggested that the 'stickiness' of calling that participants experience as priests within the Church lasts, despite any sense of discomfort with their employment, as a result of the spiritual contract manifest in their employment (Duffy et al Duffy et al 2018, 2019. This is not to conclude, however, that this is easy for participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Church has unwittingly created an othering scenario 'as it has striven to negotiate an institutional response to the secular legalisation of same-sex marriage'. 9 In July 2013, the Marriage (Same Sex Couples) Act 10 was passed, enabling same-sex couples to marry in civil ceremonies. However, Article 9 of the European Convention on Human Rights 11 guarantees religious freedom.…”
Section: Historical and Contemporary 'Othering'mentioning
confidence: 99%
“…Ia bersangkutan daripada campur tangan luar termasuk paderi sendiri iaitu Alan Wilson (Bishop Buckingham). Beliau meminta gereja-gereja di England membenarkan paderi mengahwini pasangan sesama jantina (Smith, 2019).…”
unclassified